Clinical features that need to be considered for crouzon syndrome in infancy: A rare case in Indonesia - Faustin, Febriana; Alexander, Elhant (Institute of Computer Science (IOCS), 2025)
Crouzon syndrome is a rare congenital disorder marked by premature cranial suture closure, leading to craniofacial deformities and potential neurological and respiratory complications. In Indonesia, reports are scarce, particularly in infants, and existing studies are largely limited to descriptive case reports. This study aims to describe the clinical features of Crouzon syndrome in Indonesian infants and examine the potential role of Fibroblast Growth Factor Receptor 2 (FGFR2) mutations in relation to local healthcare conditions. Using a retrospective observational case study design, data were obtained from medical records of infants with respiratory distress and swallowing difficulties since the neonatal period, complemented by radiological findings and clinical management notes. The results revealed characteristic signs such as craniosynostosis, maxillary hypoplasia, exophthalmos, and evidence of FGFR2 involvement in premature cranial bone fusion. In conclusion, early diagnosis and routine prenatal monitoring are essential to prevent severe complications, while this study contributes to the limited national literature and supports the development of more contextually appropriate diagnostic and therapeutic protocols.